2019
DOI: 10.1002/jcp.29345
|View full text |Cite
|
Sign up to set email alerts
|

FHL1 regulates myoblast differentiation and autophagy through its interaction with LC3

Abstract: Four and a half LIM domain protein 1 (FHL1) belongs to the FHL protein family and is predominantly expressed in skeletal and cardiac muscle. FHL1 acts as a scaffold during sarcomere assembly and plays a vital role in muscle growth and development. Autophagy is key to skeletal muscle development and regeneration, with its dysfunction associated with a range of muscular pathologies and disorders.In this study, we constructed FHL1-silenced or FHL1-overexpressed myoblasts to investigate its role in autophagy durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…CSRP3 (Rashid et al, 2015) and FHL1 (Han et al, 2020) have been recently found to interact with LC3B as well, but the interaction remains yet to be confirmed to be LIR-dependent.…”
Section: Unknown Specificitymentioning
confidence: 99%
“…CSRP3 (Rashid et al, 2015) and FHL1 (Han et al, 2020) have been recently found to interact with LC3B as well, but the interaction remains yet to be confirmed to be LIR-dependent.…”
Section: Unknown Specificitymentioning
confidence: 99%
“…Similarly, the overexpression of FHL1 increased myotube fusion and caused myotube hypertrophy in C2C12 cells, suggesting that FHL1 enhances skeletal myogenesis and muscle mass (19,20). On the other hand, Han et al recently reported that the knockdown of FHL1 decreased the myogenic markers, such as MyoD, MyoG, and MyHC, and reduced myotube formation in chicken primary myoblasts (24). In addition, the silencing of FHL1 increased Atrogin-1 and MuRF1, which led to muscle atrophy and wasting, unveiling the crucial roles of FHL1 in myogenic differentiation and maintenance (24).…”
Section: Discussionmentioning
confidence: 96%
“…The chicken primary myoblasts were extracted from the left breast muscle of embryonic day 11 Ross 308 broilers [13]. The primary myoblasts were cultured in the growth medium (GM), including Dulbecco's modified Eagle's medium (DMEM; Gibco, Grand Island, NY, USA), 0.5% penicillin/streptomycin (Sigma, St. Louis, MO, USA), and 15% fetal bovine serum (FBS; Gibco, Grand Island, NY, USA).…”
Section: Cell Culturesmentioning
confidence: 99%